2016
DOI: 10.1007/978-1-4939-3550-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Generation in Stars

Abstract: Enormous progress has been made on observing stellar magnetism in stars from the main sequence (particularly thanks to the MiMeS, MAGORI and BOB surveys) through to compact objects. Recent data have thrown into sharper relief the vexed question of the origin of stellar magnetic fields, which remains one of the main unanswered questions in astrophysics. In this chapter we review recent work in this area of research. In particular, we look at the fossil field hypothesis which links magnetism in compact stars to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 235 publications
1
7
0
Order By: Relevance
“…Equipartition fields of ∼2 × 10 5 G generated by a core dynamo would evolve into fields of ∼2 × 10 7 G if their flux is conserved from the MS to the WD phase. Thus, the field strengths inferred for core-dynamo-generated fields are squarely within the observed distribution of WD surface fields (Ferrario et al 2015a(Ferrario et al , 2015b. Figure 3 shows that the core convective region is restricted to mass coordinates below ≈0.5 M e for stars of M  2.5 M e .…”
Section: Magnetic Fields In Wdssupporting
confidence: 71%
“…Equipartition fields of ∼2 × 10 5 G generated by a core dynamo would evolve into fields of ∼2 × 10 7 G if their flux is conserved from the MS to the WD phase. Thus, the field strengths inferred for core-dynamo-generated fields are squarely within the observed distribution of WD surface fields (Ferrario et al 2015a(Ferrario et al , 2015b. Figure 3 shows that the core convective region is restricted to mass coordinates below ≈0.5 M e for stars of M  2.5 M e .…”
Section: Magnetic Fields In Wdssupporting
confidence: 71%
“…There are no simple equations for the conductivity for this case. In the degenerate limit the conductivity is given by the following expression [20], 4) with ρ p the proton density. In the relativistic non-degenerate high temperature limit the conductivity would be dominated by the pair plasma and be of the order of the temperature [21] which is lower than the obtained through (2.4).…”
Section: Thermodynamics Of a Protoneutron Starmentioning
confidence: 99%
“…The most popular explanations include adiabatically compressed fossil fields of the parent star and dynamo generated fields [4]. More recently it has been suggested that the magnetic field of magnetars is related to a chiral asymmetry of particles, produced during the core collapse of supernovae [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some models accounting for the generation of such magnetic fields based on, e.g., the turbulent dynamo and strong fossil fields, are reviewed in Ref. [1]. However none of these models adequately describes all the observed characteristics of magnetars.…”
mentioning
confidence: 99%